1998
DOI: 10.1007/s002590050234
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of hyperthyroidism in Austria from 1987 to 1995 before and after an increase in salt iodization in 1990

Abstract: Between 1963 and 1990, Austria had iodized salt prophylaxis of endemic goitre with 10 mg KI (7.5 mg I) per kg. This was obviously insufficient, as urinary iodine excretion ranged from 42 to 78 microg I per g of creatinine and goitre in adults remained in the endemic range of 15%-30%. Therefore salt iodization was doubled in 1990. The aim of this study was to assess the annual incidence of different types of hyperthyroidism (HT) before and after this increase in salt iodization. The incidence of HT was recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
3
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 21 publications
8
46
3
7
Order By: Relevance
“…Our results parallel the findings from Denmark that Graves' disease was the dominant type of hyperthyroidism in the area with excessive iodine intake (9). However, the similar prevalence of Graves' disease independent of the iodine intake was not in agreement with the findings from Austria (6). Other findings in our study demonstrated that the higher prevalence of hypothyroidism due to autoimmune thyroiditis (Hashimoto disease and atrophy thyroiditis) was closely related with the increase in iodine intake although no difference was found in the prevalence of thyroid autoantibodies in the general population among the three areas (17).…”
Section: Panshancontrasting
confidence: 51%
“…Our results parallel the findings from Denmark that Graves' disease was the dominant type of hyperthyroidism in the area with excessive iodine intake (9). However, the similar prevalence of Graves' disease independent of the iodine intake was not in agreement with the findings from Austria (6). Other findings in our study demonstrated that the higher prevalence of hypothyroidism due to autoimmune thyroiditis (Hashimoto disease and atrophy thyroiditis) was closely related with the increase in iodine intake although no difference was found in the prevalence of thyroid autoantibodies in the general population among the three areas (17).…”
Section: Panshancontrasting
confidence: 51%
“…The incidence of MNTG in Denmark (34.6 per 100 000 person-years) is higher than in most other countries studied, where the calculated SIRs spanned from 3.3 to 30.5 per 100 000 person-years (6,8). All these studies were performed in regions with a higher iodine intake in the population compared with Denmark.…”
Section: Subtypes Of Hyperthyroidismmentioning
confidence: 96%
“…The sensitive design used in the present study may be responsible for the high incidence compared with previous Danish studies Female 0 5 110 169 177 204 224 277 195 27 1388 Male 0 2 15 31 32 51 54 77 30 2 294 Multinodular toxic goitre Female 0 0 0 11 31 86 110 206 170 27 641 Male 0 0 1 1 4 14 18 39 21 2 100 Graves' disease Female 0 5 82 122 102 70 69 56 12 0 518 Male 0 1 12 20 21 25 17 24 162 47 901 41 506 33 092 32 420 23 355 23 506 15 257 (6,43) and above 100 after excessive iodine exposure in Tasmania (44). A comparison between these studies and the present study is difficult, as they differ with regards to the design.…”
Section: Total Incidence Of Hyperthyroidismmentioning
confidence: 99%
See 2 more Smart Citations